Attitude in Radiographic Post-Operative Assessment of Dental Implants among Italian Dentists: A Cross-Sectional Survey - Bianca Di Murro; Piero Papi; Pier Carmine Passarelli; Antonio D’Addona; Giorgio Pompa (Antibiotics, 2020)
There is a lack of evidence in the attitude and prescribing practice of implantologists in dental implant post-operative assessment; therefore, the aims of this cross-sectional study were to investigate these habits and the knowledge about radiographic aspect of retrograde peri-implantitis (RPI) among Italian implantologists. A questionnaire was sent via email to dentists randomly selected from the register of implantology and oral surgery societies. It included three questions: the preferred X-ray after implant placement, the timing of post-operative assessment and the knowledge of the RPI radiographic representation. A final sample of 434 implantologists was included in the study. The majority of them (84.3%) perform a periapical X-ray as control radiograph and picked the correct radiographic representation of RPI (74.3%), without statistically significant differences (p > 0.05) for sex, age, years of working practice and number of implants placed per year. Just 47.7% of dentists perform a control radiograph at prostheses delivery, to establish a proper baseline. A statistically significant difference (p < 0.05) was detectable only for the number of implants placed per year, with dentists placing > 80 implants selecting the correct choice. To the best of authors’ knowledge, this is the first study to report data on attitude of implantologists in radiographic imaging after implant placement.